2020
DOI: 10.1021/acs.orglett.0c03718
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light Photoredox-Catalyzed Formal [5 + 1] Cycloaddition of N-Tosyl Vinylaziridines with Difluoroalkyl Halides

Abstract: A visible-light photoredox-catalyzed formal [5 + 1] cycloaddition of N-tosyl vinylaziridines with difluoroalkyl halides as unique C1 synthons was developed. The procedure provides an efficient and practical method to synthesize diverse pyridines in moderate to good yields. The reaction underwent a radical-initiated kinetically controlled ring-opening of vinylaziridines and involved a key α,β-unsaturated imine intermediate, followed by an E2 elimination, a 6π electrocyclization, and defluorinated aromatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 85 publications
1
18
0
Order By: Relevance
“…In recent years, visible-light-promoted transformations proved to be efficient in organic synthesis because they could provide clean and inexpensive energy sources and green catalytic environments. , With the aid of photosensitizers, the substrates could be easily activated to active radical cations similar to the transformations under electrolysis mentioned above, without additional oxidants. As part of our continuous efforts in the construction of carbo/heterocyclic compounds from easily available ketene dithioacetals, we envisioned that visible-light-induced cyclizations of ketene dithioacetals with alkynes would lead to the novel [3+2] heterocyclization via the previously unknown thiavinyl 1,3-dipoles (Scheme b).…”
mentioning
confidence: 99%
“…In recent years, visible-light-promoted transformations proved to be efficient in organic synthesis because they could provide clean and inexpensive energy sources and green catalytic environments. , With the aid of photosensitizers, the substrates could be easily activated to active radical cations similar to the transformations under electrolysis mentioned above, without additional oxidants. As part of our continuous efforts in the construction of carbo/heterocyclic compounds from easily available ketene dithioacetals, we envisioned that visible-light-induced cyclizations of ketene dithioacetals with alkynes would lead to the novel [3+2] heterocyclization via the previously unknown thiavinyl 1,3-dipoles (Scheme b).…”
mentioning
confidence: 99%
“…In 2020, Li and co-workers published the first synthesis of pyridines 66 via a formal [5 + 1]-type reaction. [55] The photoredox approach used N-tosyl vinylaziridines 64 and difluoroalkyl halides 65 as C1 synthon. The transformation was catalyzed by fac-Ir(ppy) 3 under blue LED radiation.…”
Section: Recent Developments On the Photocatalytic Synthesis Of Pyridinesmentioning
confidence: 99%
“…7 Recently, Li et al reported a visible-light-driven intermolecular [5 + 1] cyclization by using bromodifluoroalkyl compounds as a C1 synthon. 8 In continuation of our interest in visible-light-driven multicomponent reactions, 9 we wondered whether it would be possible to construct the 1,3-vinylimine ion intermediate from easily available starting materials via a photocatalytic process (Scheme 1a). We speculate that enaminones, as a kind of excellent radical acceptor, 10 could be easily trapped by difluoroalkyl radicals that are generated from bromodifluoroalkyl compounds under visible-light irradiation.…”
mentioning
confidence: 99%
“…Bromodifluoroacetic acid derivatives have received significant attention in modern organic synthesis over the past decades because of their versatility and reactivity . Particularly, in the past two years, triple cleavage of bromodifluoroalkyl compounds is emerging as a promising approach in heterocyclic chemistry. In 2019, Song and co-workers reported the first example of S 8 -catalyzed triple cleavage of bromodifluoroalkyl compounds for the construction of N -heterocyclic compounds . Whereafter, the same research group developed a practical strategy for the divergent synthesis of thiazole and isothiazole derivatives from enaminoesters, S 8 , and bromodifluoroalkyl compounds .…”
mentioning
confidence: 99%
See 1 more Smart Citation